Training periodization, intensity distribution, and volume in trained cyclists: a systematic review - Galán-Rioja, M. A.; Gonzalez-Ravé, J. M.; González-Mohíno, F.; Seiler, S. (International Journal of Sports Physiology and Performance, 2023)
A well-planned periodized approach endeavors to allow road cyclists to achieve peak performance when their most important competitions are held.